Potential Applications of Nanoparticles - Abhilash M (International Journal of Pharma and Bio Sciences, 2010)
Nanoparticles (NP) are defined as particles with a diameter smaller than 100 nm, are increasingly used in different applications, including drug carrier systems and to pass organ barriers such as the blood-brain barrier. Because of their unique properties Nanocrystals (quantum dots) and other nanoparticles (gold colloids, nanobars, dendrimers and nanoshells) have been receiving a lot of attention for potential use in Therapeutics, Bioengineering and therapeutics drug discovery. In this review potential use of these Nanocrystals and Nanoparticles in various important areas has been discussed. Special properties of these nanoparticles may offer new advancement in drug discovery.